The Twenty-First Century Wars. Unconventional Conflicts Before International Law - Marsili, M. (10th Conference of the International Society of Military Science (ISMS2020) themed “Military Sciences vs. Open Sciences with the scient of COVID-19 Pandemic“, 2020)
The research aims to investigate whether and how current international customary and treaty law applies to unconventional conflicts that characterize the 21st century. The study investigates whether new rules are required, or if current rules are still valid and can be used/adapted. The research aims to check whether and to what extent states abide International Law/International Humanitarian Law in dealing with unconventional conflicts, or if, through their course of conduct, states are attempting to create new customary law, or to adapt the existing instruments to the challenges that unconventional conflicts pose. The study investigates also whether these conducts abide customaryInternational Law and peremptory norms (jus cogens), that are not consent-based, but still are obligatory upon state and non-state actors.